Comparative Numerical Study of Four Biodiesel Surrogates for Application on Diesel 0D Phenomenological Modeling - Ngayihi Abbe, Claude Valery; Nzengwa, Robert; Danwe, Raidandi (Journal of Combustion, 2016)
To meet more stringent norms and standards concerning engine performances and emissions, engine manufacturers need to develop new technologies enhancing the nonpolluting properties of the fuels. In that sense, the testing and development of alternative fuels such as biodiesel are of great importance. Fuel testing is nowadays a matter of experimental and numerical work. Researches on diesel engine’s fuel involve the use of surrogates, for which the combustion mechanisms are well known and relatively similar to the investigated fuel. Biodiesel, due to its complex molecular configuration, is still the subject of numerous investigations in that area. This study presents the comparison of four biodiesel surrogates, methyl-butanoate, ethyl-butyrate, methyl-decanoate, and methyl-9-decenoate, in a 0D phenomenological combustion model. They were investigated for in-cylinder pressure, thermal efficiency, and NOx emissions. Experiments were performed on a six-cylinder turbocharged DI diesel engine fuelled by methyl ester (MEB) and ethyl ester (EEB) biodiesel from wasted frying oil. Results showed that, among the four surrogates, methyl butanoate presented better results for all the studied parameters. In-cylinder pressure and thermal efficiency were predicted with good accuracy by the four surrogates. NOx emissions were well predicted for methyl butanoate but for the other three gave approximation errors over 50%.